2014
DOI: 10.1590/1516-635x1603233-240
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of corn batches received at a feed mill in the brazilian cerrado

Abstract: This study aimed at investigating factors that contribute to changes in the quality of corn used in compound poultry feeds. Samples were collected from 6488 bulk cargos received at a feed mill located close to Brasília, Brazil. The parameters studied were divided into two groups: those related to corn chemical composition, including crude protein (% CP), ether extract (% EE), crude fiber (% CF), nitrogen-free extract (% NFE), and estimated metabolizable energy (ME), and corn physical characteristics, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
2
6
0
2
Order By: Relevance
“…Low-quality grains showed more damage, more problems such as fragmented, broken, and grains infected by beetles, but little difference in density. The results of physical composition and grain moisture affected the corn chemical and energy content, as demonstrated by Rodrigues et al (2014), Costa et al (2015), and Hruby (2015), as corn hybrids and broiler age of determination can affect the energy content, similar to the observed in the experiment conducted by Kato et al (2011).…”
Section: Discussionsupporting
confidence: 59%
“…Low-quality grains showed more damage, more problems such as fragmented, broken, and grains infected by beetles, but little difference in density. The results of physical composition and grain moisture affected the corn chemical and energy content, as demonstrated by Rodrigues et al (2014), Costa et al (2015), and Hruby (2015), as corn hybrids and broiler age of determination can affect the energy content, similar to the observed in the experiment conducted by Kato et al (2011).…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, the ingredient quality control component of a poultry feed mill operation is an important first step in assuring a healthy diet for the birds. Alterations in the quality of feedstuffs in Brazil are some of the most important problems that the animal food industry faces and can affect feed quality and therefore animal performance (2) . Corn is the crop which occupies the largest cultivated area in Brazil and is used in both human and animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical damage in grain can occur during harvesting, drying, transport and cleaning, which may give rise to cracked and damaged grains. A series of questions should be taken in to account in the feed mill including excess humidity, presence of cracked and damaged grains, weed seeds, fire-burnt, foreign material, mould and aflatoxins (2,5) . These authors reiterate that if the corn is analyzed when it is received in the mill, 90% of the problems can be detected and they highlight the importance of the pre-cleaning analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the percentage of damaged grains was positively correlated with the presence of zearalenone, percentage of impurities and broken grains, and moisture content, whereas the percentage of impurities was positively correlated with all the evaluated physical parameters of corn. Rodrigues et al (2014) found a similar positive correlation between the undesirable physical characteristics of corn. The authors reported that physical damage increased the moisture content of grains, making them more susceptible to fungal contamination.…”
Section: Severidade De Lesões De Língua Em Frangos De Corte Associadamentioning
confidence: 53%